On the evelope and phase distribution of the mixture of signal and non-Gaussian interference - V. D. Roubtsov; A. L. Senyavskiy (Научный вестник МГТУ ГА)
For a mixture of a signal and non-Gaussian interference with arbitrary distribution law, a method of determining the envelope and phase probability densities is given. Efficiency of the proposed methods is illustrated by examples. In the case of a large signal-to-interference ratio it is shown that the distribution of the envelope for a mixture of signal and inter-ference coincides with the distribution of instantaneous value of interference shifted by a value of signal amplitude for an arbitrary distribution of interference.